PARTISIPASI PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK LAMBAN INDOMAN PUTRI (P2TP2A-LIP) DALAM PENANGANAN KEKERASAN TERHADAP ANAK DI PROVINSI LAMPUNG - Department, administratio; Sormin, Rahma Diani; Reza, Izzul Fatchu (Administratio, 2017)
ABSTRACT. The high numbers of child violence in Lampung province to create a body ofwomen empowerment and child protection (BPP&PA) province of Lampung form anintegrated Service Center Institute of empowerment of women and Children SlowlyIndoman Daughter (P2TP2A-LIP) to the province as a Centre for information, servicecenters and empowerment for women and children victims of violence. The purpose ofthis research was to know how far the participation P2TP2A-LIP in handling violenceagainst children in the province of Lampung and constraints experienced by P2TP2A-LIP inhandling violence against children in the province of Lampung. This research using thekind of research deskriftif with a qualitative approach. The result showed thatparticipation P2TP2A-LIP in the Lampung in handling of violence against children alreadyexists, both in providing information, consultation, the decision, acting together andsupporting. But P2TP2A-LIP has a constraint in handling violence against children that isstarting from the limitation of the number of human resources existing in P2TP2A-LIP togive psychic conditions of service and sacrifice itself. Keywords: Participation, P2TP2A-LIP Province Lampung, Violence Children.